Comparing the effect of psychodrama with parental behavior management skills training on social adjustment, anger and aggression of preschool children - Mitra Hoseini Khoram; Ozra Qhafari Nouran; Azar Kiamarsi (Shahid Beheshti University of Medical Sciences, 2023)
Background: Today, education and training are associated with deep, broad, and meaningful concepts which approached to serve humanity. This study aimed to compare the effectiveness of psychodrama with training parenting behavior management skills on social adjustment, anger, and aggression in preschool children. Methods: The research method was experimental with a pre-test and post-test design and a control group. The statistical population included all preschool students of Tehran-Iran (District 9) during 2020. The samples were selected through cluster sampling (n=45) and randomly assigned to experimental and control groups (n=15 each). Participants were measured through Dokhanchi social adjustment questionnaires and Anger and Aggression-Novako scale. Parental behavior management skills training programs are administered in six sessions 90 minutes for parents and psychodrama included ten 45-minute sessions for children. The control group did not receive any intervention during the study. The results were analyzed using an analysis of covariance. SPSS version 24 was used to analyze the data. Results: The results showed that the social adjustment of children in the psychodrama and the parental behavior management groups increased comparing the control group (P=0.001). Psychodrama reduced all three components of aggressive behavior, thinking, and feeling (P =0.001). The components of anger and aggression in parental behavior management have reduced significantly comparing the control group (P=0.001). Also, parental behavior management program effectiveness was significantly higher than psychodrama (P<0.05). Conclusion: The study results showed that the effect of parental management skills on reducing anger-aggression and increasing social adjustment was higher than psychodrama.